Body dissatisfaction in female adolescents: extent and correlates - Schneider, Sven; Weiß, Melanie; Diehl, Katharina (European journal of pediatrics, 2013)
This study aimed to assess the extent, patterns, and predictors of feelings of body dissatisfaction experienced by female German adolescents. Using 3D-avatar software, a sample population of 144 girls between 14 and 17 years of age was asked to estimate their actual body image, their desired body image (individual ideal), and the body image they believed their parents and their best female friend considered to be the ideal body image for them. The participants estimated their actual body mass index (BMI) to be 18.82 ± 3.01. The individual ideal body shape reported was significantly thinner, with a BMI score of 16.84 ± 2.51. Given a girl who stands 1.65 m and weighs 55 kg, this corresponds to a difference in weight of about 5.5 kg. After adjustment for the participant’s self-reported BMI, participating in an esthetic sport was correlated with a significantly lower body dissatisfaction. Conversely, low socio-economic status and the amount of time spent watching TV was correlated with a significantly higher body dissatisfaction. Negative body image-related comments made by parents were significantly associated with body dissatisfaction. The girls who participated in this study would like to be an average of 1.97 BMI units thinner. The findings presented here suggest that future intervention measures should focus on the risk groups of physically inactive girls, those who smoke, and those with a lower social status and high rates of TV consumption. Intervention measures would be especially effective in German schools which offer lower education levels and should include the pupils’ parents, who should be informed about the negative effects weight- and diet-related comments have on their children’s body images.
First online: 4. Dezember 2012
Gesehen am 19.06.2018